As representações sociais sobre desenvolvimento em Santa Maria - RS - Ribeiro, Mara Regina Rodrigues (Universidade do Vale do Rio do Sinos, 2005)
This research deals with the notion of development, which is here examined based on the main theories in the Social Sciences. Its main objective is to identify the social representations about development, through the thoughts and discourse of the social agents that dominate the economical, political and cultural spheres of the city of Santa Maria-RS, Brazil. Based on the concept these spheres have about development, this research seeks to examine how the agents perceive the city. This study on representations will allow identifying the contributions of this category to understand how everyday reality is structured and organized. In addition to that, by apprehending representations, it is possible to understand the reasons people give for their attitudes when interacting with different groups. The relevance of this research lies in the theoretical perspective used to frame the investigation. Even though there are many studies dealing with several aspects (social, political or economical) about the city of San
Keywords: desenvolvimento econômico; desenvolvimento social; representação social; Santa Maria - RS; development; social representation; Ciências Sociais Aplicadas